Cancellation of the Maanyan Dayak Traditional Engagement Agreement - Rosella Frianty; Febri Noor Hediati; Siti kotijah; Yennita Astarina; Ine Ventyrina; Hairan (Jurnal Independent, 2026)
A proposal of marriage is an attempt to bring together a man and a woman with the consent of both parties, who mutually promise to marry. The purpose of this study is to examine the implications of canceling a proposal of marriage based on the customary law of the Dayak Maanyan tribe. This study uses a non-doctrinal or socio-legal research approach through qualitative interviews with traditional leaders, processing data from primary, secondary, and tertiary legal materials. The legal implication of canceling a proposal of marriage in the Dayak Maanyan tradition is a customary sanction called sapu hirang, which is determined by the traditional leader. However, if the cancellation is for legitimate reasons, such as inappropriate behavior by one of the parties, the traditional leader can provide special consideration and adjust the sanctions imposed.